Lycopene-rich diets modulate HDL functionality and associated inflammatory markers without affecting lipoprotein size and distribution in moderately overweight, disease-free, middle-aged adults: A randomized controlled trial - McEneny, Jane; Henry, Sarah-Louise; Woodside, Jayne; Moir, Susan; Rudd, Amelia; Vaughan, Nick; Thies, Frank (Frontiers in Nutrition, 2022)
Background The consumption of lycopene-rich foods may lower cardiovascular disease (CVD) risk. Lycopene circulates in the blood bound to lipoproteins, including high-density lipoproteins (HDLs). Preliminary data from our group showed that increased consumption of tomato-based food or lycopene supplement in middle-aged subjects led to functional changes to HDL's sub-fractions, HDL2 and HDL3. These changes were also associated with a decrease in serum amyloid A (SAA), potentially enhancing their anti-atherogenic properties. Objective We carried out a comprehensive randomized controlled intervention trial with healthy middle-aged volunteers to assess whether the consumption of tomato-based foods or lycopene supplements affects HDL functionality and associated inflammatory markers, and lipoprotein subfractions size and distribution. Design Volunteers (225, aged 40–65 years) were randomly assigned to one of three dietary intervention groups and asked to consume a control diet (low in tomato-based foods, <10 mg lycopene/week), a lycopene-rich diet (224–350 mg lycopene/week), or the control diet with a lycopene supplement (70 mg lycopene/week). HDL2 and HDL3 were isolated by ultracentrifugation. Compliance was monitored by assessing lycopene concentration in serum. Systemic and HDL-associated inflammation was assessed by measuring SAA concentrations. HDL functionality was determined by monitoring paraoxonase-1 (PON-1), cholesteryl ester transfer protein (CETP), and lecithin cholesterol acyltransferase (LCAT) activities. The lipoprotein subfractions profile was assessed by NMR. Results Lycopene in serum and HDL significantly increased following consumption of both the high tomato diet and lycopene supplement (p ≤ 0.001 for both). Lycopene, either as a tomato-rich food or a supplement, enhanced both serum- and HDL3-PON-1 activities (p ≤ 0.001 and p = 0.036, respectively), while significantly reducing HDL3-SAA-related inflammation (p = 0.001). Lycopene supplement also significantly increased HDL3-LCAT activity (p = 0.05), and reduced the activity of both HDL2- and HDL3-CETP (p = 0.005 and p = 0.002, respectively). These changes were not associated with changes in the subclasses distribution for all lipoprotein fractions or the size of lipoprotein subclasses. Conclusion Our results showed that dietary lycopene can significantly enhance HDL functionality, without associated changes in particle size and distribution, by modulating the activity of HDL-associated enzymes. Concomitantly, dietary lycopene significantly decreased serum- and HDL3-associated SAA, confirming that SAA may represent a sensitive inflammatory biomarker to dietary change. Clinical Trial Register (https://www.isrctn.com), ISRCTN34203810.